Faktor-faktor yang Berhubungan dengan Stres Pengasuhan pada Ibu dengan Anak Usia Prasekolah - Lailil Fatkuriyah; Eky Madyaning Nastiti (Jurnal Kesehatan dr. Soebandi, 2022)
Introduction: Raising preschool aged children often causes stress to mothers because at this period children are still very dependent on their parents and often has behavioral problems and difficulty in managing their intense emotions.. Objective: This study aimed to determine factors associated with parenting stress among mothers with preschool aged children. Methods: A cross-sectional study design was used in this study. Sample size of this study was 118 mothers who lived in Desa Jatisari, Kecamatan Jenggawah, Kabupaten Jember, selected using convenience sampling. Data was collected using a demographic questionnaire, Parenting Stress Index-Short Form (PSI-SF), and a social support questionnaire which was developed based on Taylor's theory of social support. Statistical analysis used univariate analysis (frequency distribution) and ordinal logistic regression with statistical significance at an alpha level of 0.05.Results: There were 90 respondents who experienced moderate parenting stress. As many as 12 mothers had low parenting stress, while 16 mothers had high parenting stress. Factors related to parenting stress were mother's education (p=0.015) and social support (p=0.000). The higher the mother's education and social support received by the mother, the lower the level of parenting stress is, and vice versa. Conclusion: In this study, level of education and social support were associated to parenting stress among mothers. Cooperation between nurses, families, and local health workers is needed to provide adequate social support to mothers with preschool children. Husbands and families are expected to provide support such as direct assistance in caring for children, appreciation, and love for mothers. Nurses can also work with local health workers in providing information to mothers related to developmental tasks of family with preschool-aged children and effective stress management for mothers experiencing parenting stress so that mothers will be more adaptive and avoid physical violence against children.